Ganti Kerugian Akibat Pengadaan Tanah untuk Pembangunan Jalan Tol Jambi-Rengat - Panca Penta Silalahi, Mei; Pahlefi, Pahlefi (Zaaken: Journal of Civil and Business Law, 2023)
The purpose of this study is to determine the form of compensation given to landowners and the efforts made to settle compensation due to land acquisition for the construction of the Jambi-Rengat toll road. The problem is: What is the form of compensation given to land owners and How are efforts made to settle compensation due to land acquisition for the construction of the Jambi-Rengat Toll Road. This research uses Empirical Law research method, with primary data from land-owning communities affected by the Jambi-Rengat toll road construction project and secondary data from laws and regulations, books and other literature. The result of this study is: that the compensation received by the community affected by the Jambi-Rengat toll road project was agreed in the form of money, even though the community has agreed to the agreement the amount of money until now has not been given from LMAN (State Asset Management Institution) to the community as land owners. Efforts that can be made to complete the provision of compensation for land acquisition for the construction of the Jambi Rengat toll road refer to Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest. This effort can be done through a non-litigation approach, with reference to deliberation to reach an agreement with a fair assessment. After the agreement has been reached, further actions can involve providing compensation budgets from LMAN (State Asset Management Institutions), then continued with the provision of compensation carried out based on applicable legal procedures.